Respond to this Question
Similar Questions

Math
I need help solving the problem not the answer. (Multiple Choice) The steps below show the incomplete solution to find the value of x for the equation 7x + 8 − 3x = −6 + 10: Step 1: 7x + 8 − 3x = −6 + 10 Step 2: 7x + 8 −
asked by Ryan on March 30, 2017 
Algebra
will you please show me step by step in solving: 1/2 log b + 3 log c. I need to express as a single log logarithm and if possible, simplify Thanks
asked by sandy on December 2, 2012 
precalc
How would you find the inverse of these two functions: f(x)=4/(x4)^2 and f(x)=x^28x+16 could you please show me step by step i have been trying to figure it out for hours.
asked by Diana on July 15, 2011 
Another Problem...PLz Help COunt Iblis
Statements Reasons 1. 3x  7 = 4 2. 3x  7 + 7 = 4 + 7 3. 3x + 0 = 4 + 7 4. 3x + 0 = 3 5. 3x = 3 6. (1/3) 3x = 3 (1/3) 7. (1/3) 3x = 1 8. 1x = 1 9. x = 1 Is this problem about explaining each step? yeah like you have to write
asked by Margie... on December 2, 2006 
physics
A log is floating on swiftly moving water. A stone is dropped from rest from a 84mhigh bridge and lands on the log as it passes under the bridge. If the log moves with a constant speed of 3.6 m/s, what is the horizontal distance
asked by Randy on September 8, 2010 
Math(Please check)
The following function is onetoone; find its inverse f(x)=x^3+5 I know that the first step would be to set y = to x so I did y=x^3+5 Then you swap x with y so x=y^3+5. Then you solve for y and this is where I think i messed up.
asked by Hannah on November 3, 2010 
alg 2.
can someone please show me step by step how to do this problem... 1/2log base 4 252(3logbase4 5log base 4 25)
asked by Miley on May 8, 2008 
Help PLZ!!
consider the steps to simplify the expression. Which property is used to reach Step 3? Expression: 4 3 7 + 7 + (3 4 7 ) Step 1: = 4 3 7 + (3 4 7 ) + 7 Step 2: = 4 + ( 3 7 ) + (3) + ( 4 7 ) + 7 Step 3: = 4 + ( 3 7 ) + (
asked by Daya on August 30, 2017 
math
Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8
asked by Anonymous on October 25, 2018 
Algebra II (Matrices)
My book doesn't solve it like a linear equation, they solve it by using inverse matrices. Solve the matrix equation: 4 5m=32 1 2 n=5 A= 4 5 1 2 X= m n B= 32 5 Step 1. Find the inverse of the coefficient
asked by Jon on February 29, 2008